2008
DOI: 10.1143/jjap.47.7586
|View full text |Cite
|
Sign up to set email alerts
|

Composition Dependence in BiFeO3 Film Capacitor with Suppressed Leakage Current by Nd and Mn Cosubstitution and Their Ferroelectric Properties

Abstract: Nd,Mn)-cosubstituted BiFeO 3 (BFO) films with various Nd and Mn compositions were fabricated on a Pt/SrTiO 3 (100) substrate by pulsed laser deposition. X-ray diffraction patterns and atomic force microscopy images indicated that the suppression of impurity phases and a smooth surface morphology were realized by Nd substitution in the BFO films. Furthermore, by combining with Nd substitution, a small amount of Mn substitution in BFO films is effective for reducing the leakage current density by three orders of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
45
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(47 citation statements)
references
References 23 publications
(48 reference statements)
0
45
2
Order By: Relevance
“…Nd doping seems to reduce the "leakage" current density because Nd will substitute the Bi sites and reduce the Bi deficiency. 14,18) Next, the ferroelectric properties of the BFO and BNF cells were investigated. The BNF cell shows more rounded and poorer loops than the BFO cells, although the former shows the lower current density than the latter, as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nd doping seems to reduce the "leakage" current density because Nd will substitute the Bi sites and reduce the Bi deficiency. 14,18) Next, the ferroelectric properties of the BFO and BNF cells were investigated. The BNF cell shows more rounded and poorer loops than the BFO cells, although the former shows the lower current density than the latter, as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Many research groups have reported that a site-engineering technique using various elements is effective to suppress the leakage current in BFO films. [11][12][13][14][15][16] We proposed (Nd,Mn)-codoped BFO (BNFM) and (Pr,Mn)-codoped BFO (BPFM), and succeeded in obtaining improved electrical properties. 14,[17][18] Recently, polarization-induced photovoltaic properties in BFO films have been reported.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Yu et al 13 3 (BFM) films in a wide range of electric fields. Kawae et al 16 have studied the leakage current density of Bi 1Àx Nd x Fe 1Ày Mn y O 3 (x ¼ 0À0.07 and y ¼ 0-0.07) thin films and achieved the lowest leakage current in the films with the composition of x ¼ 0.05 and y ¼ 0.03. They also concluded that small amount of Mn substitution is very effective in reducing the leakage current, whereas excess substitution leads to an increase in leakage current.…”
Section: Introductionmentioning
confidence: 99%
“…Nd helps in suppressing the formation of secondary phases, reducing the leakage current and improving ferroelectric or magnetic properties, whereas substitution by transition metal ions (Mn þ4 ) reduces the fluctuation of the Fe valence and oxygen vacancies, which is an important factor to reduce the leakage current. [15][16][17][18][19][20][21] Based on the literature, the present doping concentration of Nd and Mn in BFO has been chosen for our studies as this composition shows lowest leakage current with enhanced electrical properties among all the substitutional compositions. 16 In this work, the main aim is to study the structural, dielectric, impedance, magnetic, and magnetoelectric properties of BNFM system.…”
Section: Introductionmentioning
confidence: 99%